Business Ethics, Coding, Compliance and Practices: Examining Findings of Old Secondary Data Analysis and Comparing Them with Current Trends (Global Journal of Management and Business Research, 2020)
This study examines the research's findings done by Value-Based Management.net, which is a management portal specifically aimed to provide the information needed by senior executives who are interested in value creation, managing for value, and valuation. This study focuses on tracing whether business ethics coding, compliance, and practices have been adequate over the past decade. It also elaborates on the impact of financial dilemmas during the beginning of the new millennium in the United States until this current time. It monitors the efforts spent by different levels of management to comply with existing codes of ethics to prevent any business misconduct in their organizations. The paper came to conclude that a new scope of the current economy and shareholders/investors' confidence aligns management's core practice with its contribution in shaping organization ethical culture. If the appropriate training and good examples are set among the organization's culture, leaders can handle many of the current challenges much easier.